Biomimetic Wood‐Inspired Batteries: Fabrication, Electrochemical Performance, and Sustainability within a Circular Perspective. (12th September 2021) - Gomez, Iñaki; Lizundia, Erlantz
Abstract: Nature's hierarchical materials offer exceptional multifunctional properties thanks to their evolution over millions of years to reach the most optimized organization in terms of function, structure, or chemistry. Exploiting the unique features of natural materials through biomimicry offers an exciting research field with large potential for new discoveries. Wood, as one of the most fascinating biomaterials, combines unique mechanical properties, an anisotropic hierarchical porosity optimized to provide rapid, and low tortuosity pathways for nutrient/water transport, abundance, and biodegradability. Accordingly, wood has inspired scientists to mimic its outstanding properties in artificial analogues to develop batteries with remarkable electrochemical performance. For instance, its sophisticated structure can be transferred to solid‐state materials through biomimetic templating to increase the lifespan and energy density of batteries, while its inherent hierarchical multi‐channeled structure allows the synthesis of current collectors with enhanced ion and electron diffusivity. This Review highlights the recent progress into the application of wood as a hierarchically porous and renewable material to develop different battery components, including the cathode, the anode, the separator, and current collectors. The potential of wood‐inspired batteries to lessen the pressure over critical raw materials and additional environmental sustainability benefits are highlighted within a circular economy perspective. Abstract : Wood has inspired scientists to mimic its outstanding properties in artificial analogues to develop batteries with remarkable electrochemical performance. This review highlights the recent progress into the application of wood as a hierarchically porous and renewable material to develop different battery components, including the cathode, the anode, the separator, and current collectors. The potential of wood‐inspired batteries to lessen the pressure over the use of critical raw materials and further environmental sustainability benefits arising from wood‐derived batteries are highlighted within a circular economy perspective.